TINDAK TUTUR SANTUN DALAM KISAH NABI YUSUF - Pratama, Oka Putra (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study aimed to describe the form of speech acts used in the Surah Yûsuf. When having a dialogue Yûsuf adjusts what form of speech acts will be used for the intended purpose to the interlocutor, and in accordance with the situation and circumstances when the speech occurs. What Yûsuf intends when speaking is different from his formal form of speech. First, the formal form of declarative aimed to request, clarify, convince, inform, warn, defend, and be grateful. Second, the formal form is imperative but can serve to honor, reject, recognition, defense, command. Third, its formal form is interrogative but can serve to resist and ask. Additionally, the Surah Yûsuf obeys Grice’s maxims of principles of cooperation and Leech's politeness scale: maxim quality, maxim of quantity, maxim of appreciation, maxim of relevance, maxim of sympathy, maxim of wisdom, maxim of simplicity (humble), maxim of consent, and maxim of generousity.